Facial asymmetry in the resting state reflects anxiety status on young males. Issue 4 (4th July 2018) - Rossi, Alessio; Formenti, Damiano; Cavaggioni, Luca; Morgante, Alice; Caruso, Palmina; Gargano, Marco; Ludwig, Nicola; Merzagora, Isabella; Alberti, Giampietro
ABSTRACT: Facial asymmetry is considered a marker of psychological, emotional and physiological distress, while anxiety is a behavioural, psychological and physiological response to a threat to well-being. Since individuals respond to anxiety with specific patterns (e.g., muscular tension), it is reasonable to hypothesize that anxiety could contribute to facial tension and therefore facial asymmetry. Instead, since facial asymmetry is perceived as "unpleasant" from peers, its presence may be a hindrance to social adaptation contributing to generate anxiety. In this study, we investigated whether resting facial asymmetry and anxiety are associated in young population. Full frontal facial photographs of 56 Caucasian males were taken in resting state to obtain indices of asymmetry in six facial landmarks. Anxiety status was assessed using the State-Trait Anxiety Inventory (STAI-Y). Analysis of the face showed that asymmetry and laterality of specific facial landmarks were associated with anxiety. State anxiety was associated with eyebrow and lateral angle of the eye, while trait anxiety was associated with eyebrow and lateral angle of the mouth. Moreover, as compared with contralateral landmarks, the left landmarks were lifted/expanded in subjects with elevated trait/state anxiety, whereas the right landmarks were lifted/expanded in subjects with low-trait/state anxiety.